Analysis of tunnel ventilation during tunnelling - a case study - Słota, Krzysztof; Słota, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the case of tunnelling by mining methods, mining regulations apply to the design of ventilation. The most important criteria to be taken into account when calculating the minimum air flow rate in a tunnel are the air velocity, the multiple exchange of air during one hour, not exceeding the permissible concentrations of gases and dust, and ensuring appropriate climatic conditions. In this paper, an analysis of ventilation methods is carried out, taking into account the parameters of fans and ventilation ducts. Changing the diameter of the duct line from 1,000 to 1,400 mm results in a 3-4-fold reduction in fan power. Adding a second twin installation reduces the ventilation power requirement fourfold. Making the duct lines parallel increases the ventilation power requirement by about 30-50% compared to two duct installations.
Keywords: tunnel; ventilation; air monitoring; tunel; wentylacja; monitoring powietrza